SeDiCI (Servicio de Difusión de la Creación Intelectual): un recorrido de experiencias (2003-2011) - De Giusti, Marisa Raquel (2010)
Created in 2003, the Servicio de Difusión de la Creación Intelectual (SeDiCI) [Intellectual Creation Diffusion Service] is the institutional repository of the Universidad Nacional de La Plata (UNLP). Its goal is to give visibility to the academic works produced at this university, since free access enable more quotations and therefore, greater impact, considering that a public institution’s key role is to socialize knowledge. Webometrics has currently ranked the SeDiCI among the 10 top digital repositories in Latin America, positioned as the leading institutional repository in Argentina. Some of the main features and services offered by the portal –from its founding to today– are presented in this document.